Meningkatkan Keterampilan Dosen Dalam Mengajar Melalui Pelatihan Pengembangan Keterampilan Teknik Instruksional PEKERTI - Hery, Cepta (LPPPI Publishing, 2024)
Technological advances are so rapid in this fast-paced era, almost affecting every aspect of life, including the world of education. With the passing of the Covid-19 pandemic and becoming the endemic it is today, it has had a big influence on changes to the teaching curriculum system, especially in universities. If we do not accompany these changes with additional scientific insight and competence (skills), both soft skills and hard skills as lecturers in higher education, of course many will experience being left behind. The author as a teaching lecturer who has not been in the teaching profession for very long and still applies some of the old methods in learning activities, often encounters obstacles in adapting and transforming knowledge where students are able to quickly explore their knowledge and know-how which they obtain through various social media. which is growing so rapidly at the moment. To compensate for this, improving the teaching skills of lecturers needs to be implemented as designed by the Directorate General of Higher Education through the Instructional Engineering Skills Development Training Program (PEKERTI) and Applied Approach (AA) which is implemented by designated state and private universities and meets the requirements in its implementation. By participating in the Instructional Engineering Skills Development Training (PEKERTI) program, it is hoped that you will be able to increase your insight and knowledge as well as the skills (competencies) that the lecturer concerned must have and can provide benefits in the form of a positive contribution to the progress of the institution or college where they carry out their activities. his learning.